EL PROGRESO, PASANDO POR EL DESARROLLO, HASTA LLEGAR AL BIENVIVIR (2016)
This article tries to explain how throughout human history have been different meanings of progress, as the welfare, happiness, quality of life, evolution.At various times, regions and communities coexist progress meanings derived from diametrically opposed theoretical, philosophical and cultural positions. Therefore, at present it is not unusual to see fanatical people who use computer technology, tablet and phone last generation, who are advocates of natural resources and the environment; others for whom it is vital to the protection of water resources, but see their progress is more noticeable if you have car and if they have economic purchasing power to buy clothes or beauty; or peasants who work for the protection of lakes, they consider that their children have a better quality of life, should be sent to study in capital cities, to avoid the same fate of their fathers, that is, engage in work the field, such as fishing, agriculture and livestock. There are others who believe that what has been seen as progress or development in the light of the Western view, it is not, because only takes into account the economic indicators and ignores the human scale development or social development, these latter are more inclined to call bienvivir these actions to improve the living conditions of communities, always in harmony with nature.